Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1177/03009858211073678
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives to animal models and their application in the discovery of species susceptibility to SARS-CoV-2 and other respiratory infectious pathogens: A review

Abstract: The emergence of the coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) inspired rapid research efforts targeting the host range, pathogenesis and transmission mechanisms, and the development of antiviral strategies. Genetically modified mice, rhesus macaques, ferrets, and Syrian golden hamsters have been frequently used in studies of pathogenesis and efficacy of antiviral compounds and vaccines. However, alternatives to in vivo experiments, such as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 184 publications
0
6
0
Order By: Relevance
“…infection of primary mucosal explants derived from different regions of the nasal cavity. 47 Histological lesions associated with SARS-CoV-2 infection in young ferrets are usually mild and gross lesions are generally absent (Supplemental Table S9). In most cases, mild rhinitis with epithelial necrosis, mild bronchopneumonia, and mild interstitial pneumonia with BALT and type II pneumocyte hyperplasia and perivascular and peribronchiolar cuffing have been described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…infection of primary mucosal explants derived from different regions of the nasal cavity. 47 Histological lesions associated with SARS-CoV-2 infection in young ferrets are usually mild and gross lesions are generally absent (Supplemental Table S9). In most cases, mild rhinitis with epithelial necrosis, mild bronchopneumonia, and mild interstitial pneumonia with BALT and type II pneumocyte hyperplasia and perivascular and peribronchiolar cuffing have been described.…”
Section: Discussionmentioning
confidence: 99%
“… 44 This hypothesis could be substantiated by further experiments, for instance by infection of primary mucosal explants derived from different regions of the nasal cavity. 47 …”
Section: Discussionmentioning
confidence: 99%
“…Another study suggested that the SARS-CoV-2 M protein induces motility, proliferation, stemness, and in vivo metastasis of triple-negative breast cancer [ 111 ]. Despite studies reporting that SARS-CoV-2 could also infect felids [ 113 ], dogs [ 114 ], and many other domestic species [ 115 ], reports on dogs or other pets exhibiting a SARS-CoV-2-induced EMT process are still lacking.…”
Section: An Overview Of Epithelial-to-mesenchymal Transition and Mese...mentioning
confidence: 99%
“…The emergence and rapid worldwide spread of SARS-CoV-2 has motivated a surge of in vitro model development for application on COVID-19 research, with cell lines derived from both humans and several other species, such as nonhuman primates. These models have been widely used for the isolation of SARS-CoV-2, the study of virus infection etiopathogenesis and the identification of potential drugs for efficient therapeutic interventions ( Runft et al, 2022 ). Up to this date, several drugs have been evaluated as potential COVID-19 therapeutic alternatives, mainly proposed as candidates based on two different strategies: empirical drug repositioning, and in vitro experiment with hypothetical or known antiviral compounds ( Izda et al, 2021 ; WHO Solidarity Trial Consortium et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%